Can Midlevel Health-Care Providers Administer Early Medical Abortion as Safely and Effectively as Doctors? A Randomised Controlled Equivalence Trial in Nepal - Warriner, I. K. (2012)
BACKGROUND: Medical abortion is under-used in developing countries. We assessed whether early fi rst-trimester medical abortion provided by midlevel providers (government-trained, certified nurses and auxiliary nurse midwives) was as safe and effective as that provided by doctors in Nepal. METHODS: This multicentre randomised controlled equivalence trial was done in fi ve rural district hospitals in Nepal. Women were eligible for medical abortion if their pregnancy was of less than 9 weeks (63 days) and if they resided less than 90 min journey away from the study clinic. Women were ineligible if they had any contraindication to medical abortion. We used a computer-generated randomisation scheme stratified by study centre with a block size of six. Women were randomly assigned to a doctor or a midlevel provider for oral administration of 200 mg mifepristone followed by 800 mug misoprostol vaginally 2 days later, and followed up 10-4 days later. The primary endpoint was complete abortion without manual vacuum aspiration within 30 days of treatment. The study was not masked. Abortions were recorded as complete, incomplete, or failed (continuing pregnancy). Analyses for primary and secondary endpoints were by intention to treat, supplemented by per-protocol analysis of the primary endpoint. This trial is registered with ClinicalTrials.gov, NCT01186302. FINDINGS: Of 1295 women screened, 535 were randomly assigned to a doctor and 542 to a midlevel provider. 514 and 518, respectively, were included in the analyses of the primary endpoint. Abortions were judged complete in 504 (97.3%) women assigned to midlevel providers and in 494 (96.1%) assigned to physicians. The risk difference for complete abortion was 1.24% (95% CI -0.53 to 3.02), which falls within the predefined equivalence range (-5% to 5%). Five cases (1%) were recorded as failed abortion in the doctor cohort and none in the midlevel provider cohort; the remaining cases were recorded as incomplete abortions. No serious complications were noted. INTERPRETATION: The provision of medical abortion up to 9 weeks' gestation by midlevel providers and doctors was similar in safety and effectiveness. Where permitted by law, appropriately trained midlevel health-care providers can provide safe, low-technology medical abortion services for women independently from doctors. FUNDING: UNDP/UNFPA/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction (HRP), Department of Reproductive Health and Research (RHR), World Health Organization.